Causes and measures of poverty, inequality, and social exclusion: A review - George E. Halkos; Panagiotis-Stavros C. Aslanidis (Economies, 2023)
Prevailing measures on the topics of monetary and non-monetary poverty-as well as economic and carbon inequality-are being critically assessed under sustainable development goals (SDGs) with a worldwide perspective. On the one hand, the poverty headcount ratio and the indices poverty gap, poverty severity, and Watts are assessed as core poverty indices. On the other hand, important inequality measures such as the Gini index and the Palma ratio are evaluated in order to find their potentials for policymaking. Furthermore, social exclusion (with the extreme forms of aporophobia and homelessness) has detrimental ramifications on human wellbeing and disturbs public provision policies. Thus, poverty, inequality, and social exclusion are integral parts of SDGs (1, 6 and 10), emphasizing the multidisciplinary nature of the above issues. Additionally, intrinsic elements of Agenda 2030 and the measuring of poverty, inequality, and polarization would significantly improve integrated policy pathways in the national and international fora.
Keywords: 330; poverty; income inequality; wealth inequality; polarization; social exclusion; homelessness; aporophobia; G20